How shifting visual perspective during autobiographical memory retrieval influences emotion: A change in retrieval orientation - Küçüktaş, Selen; St Jacques, Peggy L. (Frontiers in Human Neuroscience, 2022)
Visual perspective during autobiographical memory (AM) retrieval influences how people remember the emotional aspects of memories. Prior research in emotion regulation has also shown that shifting from an own eyes to an observer-like perspective is an efficient way of regulating the affect elicited by emotional AMs. However, the impact of shifting visual perspective is also dependent on the nature of the emotion associated with the event. The current review synthesizes behavioral and functional neuroimaging findings from the event memory and emotion regulation literature that examine how adopting particular visual perspectives and actively shifting across them during retrieval alters emotional experience, by primarily focusing on emotional intensity. We review current theories explaining why shifts in perspectives may or may not change the emotional characteristics of memories, then propose a new theory, suggesting that the own eyes and observer-like perspectives are two different retrieval orientations supported by differential neural activations that lead episodic details to be reconstructed in specific ways.